IoT Prototype System Design for Monitoring Green Mustard Microgreen Cultivation at Sayur Mini Microgreen Jakarta - Dimas Gilang Rhomadhon; Yan Sofyan (Prodi Teknologi Informasi Universitas Darma Persada, 2025)
Urban agriculture, particularly microgreen cultivation, has emerged as a strategic solution to address food needs in limited land areas. This study aims to design and evaluate an Internet of Things (IoT) prototype for monitoring the cultivation of green mustard microgreens (Brassica juncea L.) in Jakarta. The system integrates soil moisture sensors, a DHT22 sensor (temperature and humidity), a TDS (Total Dissolved Solids) sensor, and an NPK soil analyzer, enabling automated and real-time monitoring of environmental conditions. The findings indicate that the implementation of the IoT system improves water-use efficiency by up to 35% and enhances plant growth, achieving an average height of 7.2 cm with stronger root development compared to manual cultivation methods. This research provides a significant contribution to the advancement of precision agriculture in urban environments and serves as a guideline for urban farming practitioners in improving crop yield sustainably.